Staphylococcus Aureus carriage and long-term Rituximab treatment for Granulomatosis with polyangiitis - Emilio Besada; Wenche Koldingsnes; Johannes C. Nossent (PeerJ, 2015)
Objective. Chronic nasal carriage of Staphylococcus aureus (SA) increases the risk of relapse while Rituximab (RTX) is an effective agent for inducing and maintaining remission in patients with Granulomatosis with polyangiitis (GPA). We investigated whether B cell depletion and hypogammaglobulinemia that occur during RTX treatment increase the risk of chronic SA nasal carriage and subsequent disease flares, in GPA patients on long-term RTX maintenance therapy.Methods. Retrospective cohort study from a disease registry involving 29 GPA patients receiving RTX maintenance (median RTX dose of 9 g) during a median period of 49 months. Nasal swabs were collected prior and during RTX for a median of 3 and 9 swabs respectively. Persistent SA nasal carriage was defined with the presence of SA in more than 75% of nasal swabs.Results. SA nasal carriage did not change during RTX (p = 0.297). However, the rate of positive nasal swabs in GPA patients with transient SA nasal carriage during RTX maintenance increased from 0 prior RTX to 0.42 during RTX (p = 0.017). Persistent SA nasal carriage did not increase the risk of relapses (p = 0.844), of hypogammaglobulinemia (p = 0.122) and of severe infections (p = 0.144), but reduced the risk of chronic infections (p = 0.044). Change in SA carriage status during RTX did not influence the risk of relapses (p = 0.756), hypogammaglobulinamia (p = 0.474) and infections, either severe (p = 0.913) or chronic (p = 0.121).Conclusion. Long-term RTX maintenance therapy in GPA patients did not significantly influence SA nasal carriage status. Persistent SA carriage during long-term RTX treatment did not seem to increase the risk of relapses, but seemed to decrease the risk of hypogammaglobulinemia associated chronic infections.